Preparing for Industry 4.0: digital business model innovation in the food and beverage industry. (7th July 2020) - Köbnick, Philipp; Velu, Chander; McFarlane, Duncan
The digitalisation of manufacturing via Industry 4.0 initiatives will impact all industries, including food and beverage. This paper shows through a study of UK-based food and beverage manufacturers that the application of Industry 4.0 activities is mostly tactical, and thereby decoupled from the firms' business models (BM). This stems from a lack of strategic envisioning on the impact of Industry 4.0 on their entire businesses, and the prevalent efficiency-oriented corporate cultures. Findings indicate that firms need to continuously innovate their business model in order to implement I4.0. Thereby, two principles are key in adopting advanced mechatronics: (1) to granularly segment customer needs; and (2) to enhance the flexibility of value adding activities. These two principles are mutually interdependent and hence an integrated approach through continuous business model innovation will enable manufacturers to be more responsive to individual customer needs; transforming their make-and-sell BM into sense-and-act BM.